Plant growth in Arabidopsis is assisted by compost soil-derived microbial communities - Carvalhais, Lilia C.; Muzzi, Frederico; Tan, Chin-Hong; Choo, Jin Hsien; Schenk, Peer M. (Frontiers in Plant Science, 2013)
Plants in natural and agricultural environments are continuously exposed to a plethora of diverse microorganisms resulting in microbial colonization of roots and the rhizosphere. This process is believed to be accompanied by an intricate network of ongoing simultaneous interactions. In this study, we examined Arabidopsis thaliana roots and shoots in the presence or absence of whole microbial communities extracted from compost soil. The results show a clear growth promoting effect on Arabidopsis shoots in the presence of soil microbes compared to plants grown in microbe-free soil under otherwise identical conditions. Element analyses showed that iron uptake was facilitated by these mixed microbial communities which also led to transcriptional downregulation of genes required for iron transport. In addition, soil microbial communities suppressed the expression of marker genes involved in nitrogen uptake, oxidative stress/redox signaling, cell wall modification and salicylic acid (SA)-mediated plant defense while upregulating jasmonate (JA) signaling and photosynthesis. Multi-species analyses such as simultaneous transcriptiptional profiling of plants and their interacting microorganisms (metatransciptomics) coupled to metagenomics may further increase our understanding of the intricate networks underlying plant-microbe interactions in their diverse environments.